The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1101/667295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SRSF3 confers selective processing of miR-17-92 cluster to promote tumorigenic properties in colorectal cancer

Abstract: Almost a half of microRNAs (miRNAs) in mammalian cells are generated from polycistronic primary transcripts encoding more than one miRNA. Mature miRNAs from polycistronic clusters frequently regulate complementary sets of target mRNAs. How the processing of individual miRNAs within the clusters is controlled to give rise to distinct miRNA levels in vivo is not fully understood. Our investigation of SRSF3 (Serine-Arginine Rich Splicing Factor 3) regulated noncoding RNAs in pluripotent cells identified miR-17-92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…SRSF3 was also identified with pri-mir-17 (Figure S5D), which has a CNNC motif (CCUC) (Figures 6F and S5E). Moreover, a recent study showed that SRSF3 KO results in a strong reduction in the miR-17 level (Ratnadiwakara et al, 2019). On the basis of these observations, we tested if SRSF3 is required for the productive processing of pri-mir-17 by performing in vitro assay.…”
Section: Srsf3 Induces Alternative Processing Of Mir-142 and Prevents...mentioning
confidence: 98%
“…SRSF3 was also identified with pri-mir-17 (Figure S5D), which has a CNNC motif (CCUC) (Figures 6F and S5E). Moreover, a recent study showed that SRSF3 KO results in a strong reduction in the miR-17 level (Ratnadiwakara et al, 2019). On the basis of these observations, we tested if SRSF3 is required for the productive processing of pri-mir-17 by performing in vitro assay.…”
Section: Srsf3 Induces Alternative Processing Of Mir-142 and Prevents...mentioning
confidence: 98%
“…SR proteins also interact with non-coding RNAs, such as small nucleolar RNAs (snoRNAs), microRNA (miRNAs) and long non-coding RNAs (lncRNAs) [ 43 , 60 ]. Binding of SRSF1 and SRSF3 promotes miRNA processing by enhancing Drosha-mediated cleavage in a splicing-independent manner [ 8 , 27 , 33 , 39 ]. SRSF1 regulates maturation of miR-7, which targets the 3′UTR of SRSF1 and represses its own translation [ 61 ].…”
Section: Sr Proteins and Non-coding Rnasmentioning
confidence: 99%